S-BPM ONE Setting the Stage for Subject-Oriented Business Process Management First International Workshop, Karlsruhe, Germany, October 22, 2009. Revised Selected Papers - Buchwald, Hagen.; Fleischmann, Albert.; Seese, Detlef.; Stary, Christian. (Communications in Computer and Information Science, 2010)
This book constitutes the refereed proceedings of the First Workshop on Subject-Oriented Business Process Management, S-BPM ONE 2009, held in Karlsruhe, Germany, in October 2009. The papers are organized in topical sections on visionary engagements; essential capabilities; and penetration perspectives.